2004
DOI: 10.1111/j.1742-1241.2004.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and inflammatory markers in Alzheimer's and vascular dementia

Abstract: Alzheimer's disease is classified as a degenerative dementia while vascular dementia is known to be associated with atherothrombosis and classical vascular risk factors. However, over the last decade, there is increasing evidence of the role of haemostatic factors and inflammatory mechanisms in the pathogenesis of Alzheimer's disease. Serum markers of hypercoagulability and markers of inflammation could lead to thrombosis, accelerated atherogenesis and resulting dementia of both Alzheimer's and vascular dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 61 publications
1
59
0
2
Order By: Relevance
“…History of tobacco use also was associated with worse cognitive functional outcome in patients with atherothrombosis, an effect that cannot be clearly explained. However, smoking has been shown to be a risk factor for dementia 38 and to increase the levels of serum markers for coagulation and inflammation, 39 which consequently induces leukoaraiosis 40 ; thus, we assume that a similar mechanism exists for the apparent effect of smoking history on decreased cognitive functional outcome in patients with atherothrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…History of tobacco use also was associated with worse cognitive functional outcome in patients with atherothrombosis, an effect that cannot be clearly explained. However, smoking has been shown to be a risk factor for dementia 38 and to increase the levels of serum markers for coagulation and inflammation, 39 which consequently induces leukoaraiosis 40 ; thus, we assume that a similar mechanism exists for the apparent effect of smoking history on decreased cognitive functional outcome in patients with atherothrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this traditional classification, there is increasing evidence of the common role of haemostatic factors and inflammatory mechanisms in the pathogenesis of both vascular dementia and AD. In fact, many of the risk factors for cerebrovascular disease and vascular dementia, including serum total cholesterol, hypertension, atherosclerosis and Apolipoprotein E (ApoE) genotype, have also been shown to increase the risk of AD (Panza et al 2005, Gupta et al, 2005. Furthermore, longitudinal studies demonstrated a significant increase in the risk of developing AD in cohorts of hypertensive patients compared to normotensive subjects, suggesting that extensive peripheral atherosclerosis is a risk factor for AD (Vogel et al 2005, Newman et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Of these various paradigms, the notion that spontaneous emboli, most likely due to systemic hypercoagulability, is of particular interest. AD patients have been documented to have abnormally increased activated Factor VII, von Willebrand factor and prothrombin 1+2 fragment in their circulation [13], the substrate and result of intravascular thrombin generation. Of interest, while patients with AD were noted to have fibrinogen concentrations that on average were not abnormally increased [13], another *Address correspondence to this author at the Department of Anesthesiology, the University of Arizona College of Medicine, P.O.…”
Section: Introductionmentioning
confidence: 99%
“…AD patients have been documented to have abnormally increased activated Factor VII, von Willebrand factor and prothrombin 1+2 fragment in their circulation [13], the substrate and result of intravascular thrombin generation. Of interest, while patients with AD were noted to have fibrinogen concentrations that on average were not abnormally increased [13], another *Address correspondence to this author at the Department of Anesthesiology, the University of Arizona College of Medicine, P.O. Box 245114; 1501 North Campbell Avenue, Tucson, AZ 85724-5114, USA; Tel: (520) 626-7195; Fax: (520) 626-6943; E-mail: vgnielsen@email.arizona.edu work noted that patient with mild cognitive impairment were at greater risk of more rapid advancement to AD if their circulating fibrinogen concentration was >300 mg/dl [14].…”
Section: Introductionmentioning
confidence: 99%